Healthcare utilization and economics evaluation of paliperidone palmitate once-monthly in schizophrenia: a one-year, real-world, and retrospective mirror image study in China - Zhou, Yixiang; Chen, Binbin; Huang, Yinghua (Frontiers in Psychiatry, 2024)
Background Investigation and analysis of the changes in healthcare resources and burden of schizophrenia in the real world before and after switching from oral antipsychotics (OAPs) to paliperidone palmitate once-monthly (PP1M) could provide evidence to clinicians and patients for choosing treatment modality and data support for health policy optimization Methods The first dosage of PP1M was set as mirror point, and patients with mirror point between January 2020 and June 2022 were recruited in the study. The differences in treatment patterns, healthcare resource utilization, and costs within one year before and after the mirror point were compared. Results A total of 72 patients transitioning from OAPs to PP1M (mean age, 35.33 years; 43.06% female) were included in the study. Of the 72 patients, the application of PP1M resulted in a significant reduction in the hospitalization times, emergency room visits, and direct medical costs (P < 0.001), while the pharmacy cost and total cost increased by 222.57% (P < 0.001) and 16.35% (P < 0.001), respectively; PP1M accounted for 88.48% of the pharmacy cost. For patients with ≥1 hospitalization during the OAPs phase (n = 25), the number of hospitalizations, hospitalization days and hospitalization expenses decreased by more than 90% (P < 0.001). Total one-year expenses decreased by 37.67% (P < 0.001), and pharmacy expenses increased by 185.21% (P < 0.001). For patients with no hospitalizations during the OAPs phase (n = 47), emergency and outpatient visits decreased by 70% (P < 0.001) and 30.27% (P < 0.05), respectively, while the total cost increased by 117.56% (P < 0.001), and the pharmacy cost increased by 260.15% (P < 0.001) after initiation of PP1M treatment. Conclusion After the transition to PP1M, the number of hospitalizations and outpatient and emergency department visits reduced, and healthcare resources were conserved. Switching to PP1M may be more economically beneficial for patients with prior hospitalizations while on OAP regimens. The high price of PP1M might be an obstacle to its widespread use.